Assessment of G6PD Level among Type 2 Diabetes Mellitus Patients and Its Relationship to Demographic and Clinical Data - Waleed Ali , Widad; Al-Awadi , Najlaa (Hammurabi Journal of Medical Sciences, 2024)
Background: Glucose-6-phosphate dehydrogenase is the rate-limiting enzyme of the pentose phosphate pathway. Because it produces the coenzyme nicotinamide adenine dinucleotide phosphate, the major cellular reductant and fuel for glutathione recycling within the cells, it is necessary for antioxidant defense. Diabetes mellitus is a metabolic disorder marked by hyperglycemia caused by insulin metabolism problems. Type 2 diabetes mellitus, which was previously referred to as non-insulin dependent diabetes mellitus (NIDDM) or “adult-onset diabetes” is claimed to be caused by insulin resistance, a disease in which cells fail to adequately utilize insulin, which can be paired with an absolute insulin deficit or diminished insulin output. It was discovered that diabetes mellitus and high glucose levels reduce G6PD activity. Objectives: The aim of the study is to assess the G6PD level among type 2 DM patients and correlate the G6PD level with demographic and clinical data. Materials and Methods: This cross-sectional study included 100 patients with type 2 DM who are receiving therapy at the Diabetic Center of Marjan Teaching Hospital in Babylon. The current study included patients with established diagnosis of type 2 DM and HbA1c ≥ 7%. Demographic and clinical data include (age, sex, body mass index, physical activity, alcoholic intake, smoking, duration and type of treatment for DM, medical history include Family history of G6PD, hematological disease (sickle cell trait\disease, thalassemia), adrenal disorder, autoimmune disease (lupus, rheumatoid arthritis), hypertension, coronary artery disease, thyroid disease , splenectomy and chronic use of other drugs).Investigations (G6PD level, FPG,2-h PG, HbA1c and lipid profile) will be collected at the time of the sampling. Results: There was no significant difference (P value > 0.306) in G6PD level according to age of type 2 DM patients. There was no significant difference (P value > 0.721) in G6PD level according to sex of type 2 DM patients. There was significant negative correlation between G6PD level and study markers of glycemic control among type 2 DM patients. There was no significance correlation between G6PD level and lipid profile among type 2 DM patients. There was no significant difference of G6PD level according to history of hypertension among type 2 DM patients. Conclusions: Poor glycemic control was associated with lower G6PD activity which may be associated with several health problems.